Development of a Chatbot with NLP for the Prefecture of Los Rios in Ecuador - Johanna, L. Sanchez C. (2022)
The coronavirus has prevented face-to-face consultations of procedures in the entities, so Ecuadorian companies have opted to use technological tools to provide smooth service to their customers. Among them is the Chatbot, which allows users to receive personalized attention through a computer. This paper presents the development of a chatbot for the Prefecture of Los Rios in Ecuador. The main objective is to present the development of a chatbot for the attention and management of services offered to citizens of the Prefecture of Los Rios. Direct research for collecting the necessary information and a qualitative approach study for the development of this project involved interviews in learning about the needs and requirements of citizens. The Chatbot Prefectura Los Ríos uses frameworks for natural language processing developed from a Dialog flow tool, resulting in users' acceptance.